Photodegradation of S-metolachlor using metal oxide doped tungsten oxide under visible light - Horiean, Linda; Sakonwaree, Thanyaluck; Sirichaiwattananun, Nontaporn; Rangsunvigit, Pramoch; Termtanun, Mutsee (Science, Engineering and Health Studies, 2021)
In this research, tungsten oxide (WO3) nanoparticles were modified by doping oxide of bismuth (Bi), vanadium (V), or manganese (Mn) at 0.5, 1, 2% (w/w). The undoped WO3 and Bi/V/Mn oxide doped WO3 were synthesized by using sol-gel method to find out the suitable metal loading amount for S-metolachlor degradation. After synthesis, the methods and techniques were performed for characterization the prepared catalysts. The photocatalytic activities of undoped and doped WO3 samples in catalyzing S-metolachlor degradation under visible light were determined. After 4 h reaction, ultraviolet-visible (UV-Vis) spectroscopy was performed to observe the remaining concentration of S-metolachlor. From the characterization results, WO3 had larger surface area and crystalline size after loading Bi/V/Mn oxide, but with the less electrons-holes recombination. Among three different doped metal oxides and different doping quantities, 1% (w/w) Bi2O3 doped WO3 had the least electrons-holes recombination rate and provide the highest photocatalytic efficiency with 55.43% S-metolachlor degradation for a period of 4 h under visible light. Furthermore, the reusability of doped-photocatalysts was also examined to check the deactivation possibility. There was approximately 3% decrease in photoactivity of 1% (w/w) Bi2O3 doped WO3 after repeating photodegradation of S-metolachlor for 3 times.